Measuring the effectiveness of the Chinese Certified Emission Reduction scheme in mitigating CO2 emissions: A system dynamics approach. (20th April 2021) - Ye, Fei; Xiong, Xueying; Li, Lixu; Li, Yina
Abstract: As an emerging carbon offset mechanism, the Chinese Certified Emission Reduction (CCER) scheme can theoretically supplement the emissions trading scheme (ETS) to alleviate global warming. However, due to poor data availability and short implementation time, little effort has been made to understand the mechanism and driving factors of the CCER scheme. To fill these gaps, this paper establishes a system dynamics model with feedbacks to analyze the coupling effects of the ETS and the CCER scheme. Three scenarios, including a baseline scenario (BAU scenario), a single trading market scenario (i.e., ETS market only), and a double trading market scenario (i.e., both the ETS market and the CCER market), are considered. The simulation results reveal that compared with the BAU scenario, both the single trading market scenario and the double trading market scenario can accelerate the mitigation of CO2 emissions, reduce abatement costs, and transform the energy structure. Interestingly, in the double trading market scenario, although CO2 emissions are slightly higher and the renewable energy proportion is slightly lower than that in the single trading market scenario, the additional cost-saving effect of the double trading market scenario over time increases significantly. Besides, to fulfill the Intended National Determined Contributions (INDCs) as closely as possible, governments need to set a rational offset rate of CCER quotas and to stabilize the carbon quota trading price. These findings enrich the relevant knowledge in the field of climate change by providing implications for the design of novel carbon offset instruments.